PHYSICO-CHEMICAL AND SENSORY EVALUATION OF CAPE GOOSEBERRY FRUITS (Physalis peruviana L.) - Carlos J. MÁRQUEZ C. (Universidad de Antioquia, 2009)
Cape gooseberry fruits are harvested at maturity for consumption at three different times. They are evaluated physico-chemically and sensorially. Repeated measures analysis are performed using a variancecovariance structure of the first order autoregressive heterogeneous. The results show statistically significant differences (p0,05) for aroma, texture, mouth taste and flavors variables. The accesions studied for the phytoimprovement program of the physical, chemical and organoleptic characteristics were similar to the commercial samples. Therefore it is expected that crosses between them do not invalidate the exercise.